Blind Navigation System By Using RFID And Digital Compass Technology - Anuar, Mohamed Kassim; Takashi, Yasuno; Shukor, Ahmad Zaki; Chan, Xin Zhi; Jo Jo Sam, Wai Lun (2014)
This paper describe the RFID technology which is applied to guide the visually impaired person at indoor and outdoor environment. In order to provide an efficient and user-friendly navigation tools, it is proposed to design and develop a navigation device using RFID network with the digital compass to guide visually impaired person walking properly via audio navigation. The idea of positioning and localization with digital compass and direction guiding through voice commands is implemented in this design. The study focuses on the calibration of the compass and relocates the visually impaired person back to the normal route if they are out of the direction. Data analysis will be done during the evaluation of the navigation device and assessment will be made improve the performance of the device. This project is beneficial to visually impaired person because the navigation device designed with voice commands will helps them to have a better, safer and comfortable travel.